Quantitative determination of MS-induced corpus callosum atrophy in vivo using MR imaging. - Simon, J H; Schiffer, R B; Rudick, R A; Herndon, R M (American Journal of Neuroradiology, 1987)
To quantitate the extent of corpus callosum atrophy in multiple sclerosis, midsagittal corpus callosum areas were determined in 48 controls with normal MR scans and 41 patients with definite multiple sclerosis. The mean midsagittal corpus callosum area was 601 mm2 (range 405-791), 641 mm2, and 561 mm2 for all adult controls, for adult males, and for adult females, respectively. Control values were significantly greater than the means determined for all multiple sclerosis (MS) patients (508 mm2, range 281-758), for MS men (528 mm2), or for MS women (498 mm2). The degree of corpus callosum atrophy paralleled the estimated volume of periventricular and corpus callosum high-signal lesions, suggesting a possible cause-effect relationship. The results indicate that corpus callosum atrophy occurs commonly in patients with typical clinical forms of multiple sclerosis.